Living with Monsters Ethnographic Fiction about Real Monsters - Musharbash, Yasmine; Gershon, Ilana (punctum books, 2023)
For every generic type of monster-ghost, demon, vampire, dragon-there are countless locally specific manifestations, with their own names, traits, and appearances. Such monsters populate all corners of the globe haunting their humans wherever they live. Living with Monsters is a collection of fourteen short pieces of ethnographic fiction (and a more academically inclined introduction and afterword) presenting a playful, spirited, and engaging look at how people live with their respective monsters around the world. They focus on the nitty-gritty dos and don'ts of how to placate spirits in India; how to domesticate Georgian goblins, how to live with aliens, how to avoid being taken by Anito in Taiwan, while simultaneously illuminating the politics of monster-human relations. In this collection, anthropologists working in fieldsites as diverse as the urban Ghana, the rural US, remote Aboriginal Australia, and the internet present imaginative accounts that demonstrate how thinking with monsters encourages people to contemplate difference, to understand inequality, and to see the world from new angles. Combine monsters with experimental ethnography, and the result is a volume that crackles with creative energy, flouts traditions of ethnographic writing, and pushes anthropology into new terrains.